Nachhaltige Exportwirtschaft durch Umweltstandards? Neue Handelsstrukturen auf dem US-amerikanischen Kaffeemarkt - Dünckmann, Florian (ERDKUNDE, 2003)
This contribution analyses the trade and the marketing of environmentally friendly coffee on the American market, the largest single consumer market in the world. The standards for organic production as well as the Bird-Friendly Coffee and the Eco-OK seals will be discussed. These standards not only vary in their environmental specifications, but they also each have a very different market potential: while the coffee from certified organic production can serve an existing customer base, the other two seals need first to create a respective demand and consequently command a much smaller market share. The individual standards stand, like individual companies, in competition with one another, which makes a potential merger into one overarching standard very unlikely. In the United States the environmentally friendly sector is embedded in a rapidly expanding speciality coffee sector that has proven to be very receptive to the idea of environmental standards. But the speciality sector is moving from a growth phase into a maturity phase and is marked by massive concentration processes. The environmentally friendly trade thus stands at a crossroads: either the sector remains restricted to a small, decentrally structured niche market that offers a kind of reserve for small coffee producers; or it will develop into a mass market dominated by large corporations. This kind of expansion in the environmentally friendly market would, on the one hand, be tied to positive environment effects. On the other hand, the sector would lose the advantages of a decentrally structured market (power balance in the chain of production, predisposition to innovation, concentration on quality etc.).